Mechanical Strength of Hybrid Laminate Composite Glass/Carbon Fibers on Savonius Blade Turbine Application - Sukri, Niam; Yudhanto, Ferriawan; Shomad, Muhammad Abdus; Anugrah, Rinasa Agistya (Universitas Muhammadiyah Yogyakarta, 2022)
Introduction – VI (Vacuum Infusion) method. The HLC consist of 1 ply carbon woven roving carbon 4 plies glass fiber woven roving (WR-WR), and another variation is 1 ply carbon woven roving and 4 plies glass fiber chopped strand mat (WR-CSM). The different types of glass fiber on the carbon woven roving of HLC is objecting to this research. The manufacture of HLC by VI using 0.8 Bar pressure to flow the polyester resin. The panel HLC cutting according to the ASTM (American Standard Testing and Material) D3039 for tensile strength and ASTM D790 for the flexural test of HLC. The HLC mechanical strength depends on the excellent bonding in the interfacial laminate stress. The direction of WR-WR gives a good effect against tensile load, and the fracture after the test is minor multiple cracks (ductile) and lowest delamination fracture. The WR-WR has the highest tensile stress and modulus by 162.9 MPa and 5.2 GPa, respectively. The flexural test has been resulted in the highest modulus by 8.8 GPa. These mechanical characteristics according to applicated on Savonius Blade Turbine. Purpose – Knowing the mechanical strength of the Carbon/Glass-reinforced hybrid laminate composite, which is suitable for application to the savonius turbine blade Methodology/Approach – We are composing one carbon fiber and four glass fibers in a WR-CSM and WR-WR arrangement. The process of making hybrid laminate composite with the Vacuum Infusion method. Findings – The result of this research is to choose a fiber arrangement that has high mechanical strength and good bonding between fiber layers. Originality/ Value/ Implication – The composite manufacture with vacuum infusion process produces a thin product which light and strong properties.